Biophysics : a physiological approach - Dillon, Patrick F., 1951- (Cambridge, UK ; New York : Cambridge University Press, 2012)
'Specifically tailored to life science students, this textbook explains quantitative aspects of human biophysics with examples drawn from contemporary physiology, genetics, and nanobiology. It outlines important physical ideas, equations, and examples at the heart of contemporary physiology, along with the organization necessary to understand that knowledge. The wide range of biophysical topics covered include energetics, bond formation and dissociation, diffusion and directed transport, muscle and connective tissue physics, fluid flow, membrane structure, electrical properties and transport, pharmacokinetics, and system dynamics and stability. Enabling students to understand the uses of quantitation in modern biology, equations are presented in the context of their application, rather than derivation. They are each directed toward the understanding of a biological principle, with a particular emphasis on human biology.'--p. [4] of cover.
The energy around us -- Molecular contacts -- Diffusion and directed transport -- Energy production -- Force and movement -- Load bearing -- Fluid and air flow -- Biophysical interfaces : surface tension and membrane structural properties -- Membrane electrical properties -- Agonist activation and analysis -- Stability, complexity and non-linear systems.
Includes bibliographical references and index.
Keywords: Biophysics; Biophysical Phenomena